The impact of perindopril and metformin on the markers of endothelial dysfunction in rats with acute intracerebral hemorrhage and type 2 diabetes mellitus - Zhyliuk, V.I.; Lievykh , A.E.; Shevtsova , A.I.; Tkachenko , V.A.; Kharchenko, Yu.V. (Medicni Perspektivi, 2021)
This comparative research is aimed to study the effect of perindopril and metformin on the levels of biochemical markers of endothelial dysfunction in rats with type 2 diabetes mellitus (T2DM) complicated by a brain hemorrhage. The study was carried out on 30 white male Wistar rats. T2DM was simulated by a single intraperitoneal injection of nicotinamide and streptozotocin (NA/STZ). Intracerebral hemorrhage (ICH) was induced by microinjection of 1 μL of bacterial collagenase 0.2 IU/μL into the striatum on the 60th day of the experiment. Animals were randomized into 5 groups: A – negative control (intact, n=6); B – positive control 1 (NA/STZ, n=6); C – positive control 2 (NA/STZ+ICH, n=6); D – perindopril (“Prestarium”, 2 mg/kg+NA/STZ+ICH, n=6); E – metformin (“Siofor”, 250 mg/kg+NA/STZ+ICH, n=6). The studied drugs were administered intragastrically for 20 days, starting from the 50th day after the induction of T2DM. Endothelial function was assessed by the content of homocysteine (Hcy), advanced glycation end products (AGEs), endothelin-1 (ET-1), and von Willebrand factor (vWF) in blood serum. It was found that long-term separate T2DM is accompanied by hyperhomocysteinemia, as well as an increase in AGEs, ET-1, and vWF levels, indicating dysregulation of the hemostasis system and vascular tone. It should be noted that brain hemorrhage in T2DM can enhance these manifestations, although the obtained differences were characterized only by a persistent trend. At the same time, the effect of perindopril was limited only by a significant decrease in AGEs levels by 31.2% (p<0.05). In turn, the action of metformin was characterized by a positive glycemic control, as well as an effect on the state of the vascular endothelium, namely, a significant decrease in AGEs, ET-1 and vWF levels by 37.6% (p<0.05); 5.5% (p<0.05) and 9.5% (p<0.05), respectively. It was also found that the endotheliotropic properties of the studied drugs were not associated with an effect on homocysteine levels. Thus, metformin in conditions of diabetes mellitus complicated by acute intracerebral hemorrhage has advantages over perindopril in relation to endothelial dysfunction.